THE ROLE OF MANAGEMENT PRACTICES IN ENHANCING NUTRITIONAL OUTCOMES IN INSTITUTIONAL FOOD SERVICES (International Journal of Food and Nutritional Sciences, 2021)
Abstract: Institutional food services, prevalent in schools, hospitals, and large organizations, are pivotal in shaping dietary habits and overall health. Effective management practices significantly enhance nutritional outcomes in these settings. This paper examines how management practices—menu planning, staff training, quality control, procurement, and customer engagement—impact the nutritional quality of institutional food services. Strategic menu planning ensures adherence to nutritional guidelines and accommodates diverse dietary needs, while comprehensive staff training fosters knowledge of nutrition and food safety. Rigorous quality control measures maintain high standards in food preparation and handling. Efficient procurement and supply chain management contribute to the use of high-quality ingredients, and incorporating customer feedback helps tailor services to meet consumer preferences. Through case studies, the paper illustrates successful implementations of these practices and discusses challenges such as budget constraints and resistance to change. Solutions, including technological advancements and collaborative efforts, are proposed to overcome these challenges. The paper concludes that optimized management practices are essential for improving nutritional outcomes and public health in institutional food services, highlighting the need for ongoing research and innovation in this field.